1987
DOI: 10.1113/jphysiol.1987.sp016782
|View full text |Cite
|
Sign up to set email alerts
|

The discharges of cerebellar Golgi cells during locomotion in the cat.

Abstract: SUMMARY1. Extracellular recordings have been obtained from 134 units in the paravermal cortex of lobule V in the anterior lobe of the cerebellum in free-to-move cats. Each unit discharged action potentials in a characteristic pattern with no complex spikes. Previous investigators have described such discharges and have assigned them to Golgi cells. We provide further evidence to support this identification.2. In cats which were sitting quietly, each putative Golgi cell discharged tonically at a low rate (overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
84
3
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 23 publications
15
84
3
2
Order By: Relevance
“…It should however be noted that GCs largely outnumber the Lugaro cells in the granular layer [the ratio of Golgi to Lugaro cells is ϳ67/15 in the mouse cerebellum according to Simat et al (2007)]. Finally, unlike previously reported (Edgley and Lidierth, 1987), we did not find that PC action potentials were shorter than those of GCs (Fig. 3D) were.…”
Section: Identification Of Golgi Cells and Mossy Fiberscontrasting
confidence: 56%
See 4 more Smart Citations
“…It should however be noted that GCs largely outnumber the Lugaro cells in the granular layer [the ratio of Golgi to Lugaro cells is ϳ67/15 in the mouse cerebellum according to Simat et al (2007)]. Finally, unlike previously reported (Edgley and Lidierth, 1987), we did not find that PC action potentials were shorter than those of GCs (Fig. 3D) were.…”
Section: Identification Of Golgi Cells and Mossy Fiberscontrasting
confidence: 56%
“…The axonal plexus of individual GCs are known to branch within generally nonoverlapping parasagittal planes (Barmack and Yakhnitsa, 2008). Combined with the heterogeneity of their discharge patterns, this suggests, as previously speculated by Edgley and Lidierth (1987), that subpopulations of thousands of GrCs organized in sagittal zones are under different patterns of inhibitory control. van Kan et al (1993) reported that most MFs responded reciprocally to extension and flexion movements and exhibited strong device specificity (showed preference for shoulder, elbow, wrist, or finger manipulation), whereas GCs fired identically for both flexion and extension, and lacked device specificity.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations